2016
DOI: 10.3139/113.110445
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Detergent Efficiency and Mechanism by Real-Time Measurement Using a Novel and Tailored QCM-D methodology

Abstract: Currently there is a lack of knowledge on how to scientifically and rapidly screen new detergent formulations. To address this, we employed the Quartz Crystal Microbalance with Dissipation technique which allows real-time acquisition of the cleaning process. Using an automated multichannel setup enabled rapid, simultaneous screening of eight formulations in regard to cleaning rate, soil swelling and soil removal. Herein, 9 commercially available dishwashing formulations are screened and ranked based on their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Interestingly, the adsorption experiment of SEKL solution at pH 7 resulted in an increase, rather than a decline in f (Figure ), which shows the desorption of SEKL from the surface, instead of its adsorption onto the surface . This can happen when a hydrophobic segment of SEKL interacts with xylene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the adsorption experiment of SEKL solution at pH 7 resulted in an increase, rather than a decline in f (Figure ), which shows the desorption of SEKL from the surface, instead of its adsorption onto the surface . This can happen when a hydrophobic segment of SEKL interacts with xylene.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly,t he adsorption experiment of SEKL solution at pH 7r esulted in an increase, rather than ad ecline in f (Figure 6), which shows the desorption of SEKL from the surface, instead of its adsorption onto the surface. [62,63] This can happenw hen ah ydrophobic segment of SEKL interacts with xylene.H owever,t he higherh ydrophilicity of SEKL ( Figure 5) at this pH keeps it in the water phase and desorption of oil occurs via the aqueous flow in the chamber.I ndeed, SEKL functions as ad etergent/surfactant in removing the oil droplets from the substrate. The fact that this removal happened at neutralp Hw ould introduce SEKL as ap otential biomaterial for the formulation of novel safe detergents.…”
Section: Rheological Characteristicsmentioning
confidence: 99%
“…First, the kinetics of Cu corrosion was monitored over time using the distribution of changes in f5 (i.e., changes of f5 every minute or denoted as Δf5 d ) (Calculation S1). Numerous studies indicated that changes in f (Δ f ) provide qualitative information about dynamic changes over the surface, and that increase in Δ f corresponds to a decrease in accumulated mass on the surface. ,, , The increase in mass could be attributed to the accumulation of Cu­(I) and Cu­(II) corrosion byproducts and/or deposition of other minerals on the Cu sensor surface. In our study, it was impossible to distinguish the specific source of mass increase; however, given the simplicity of the test water makeup, it was unlikely that solids other than Cu corrosion byproducts would precipitate under the experimental conditions over the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Quartz (SiO 2 ) crystal microbalance with dissipation (QCMD) monitoring can continuously capture the in situ nanoscale changes resulting from interfacial interactions and chemical reactions over surfaces via monitoring the change of resonating frequency and energy dissipation of a piezoelectric quartz crystal disk with a reasonable time resolution (usually within a few hours). The QCMD has been widely applied in diverse fields, and some of the specific areas include studying cell adhesion and spreading, , membrane permeability, nanoparticle deposition mechanisms under different flowing conditions, detergent efficiency, and biological materials and bioengineered surfaces. , However, QCMD studies on Cu corrosion in drinking water chemistry are still lacking. Choi first used QCMD to examine the etching or dissolution rate of Cu exposed to deionized water at pH 2.0–10.0, which does not represent the typical drinking water chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Other topics attracting great interest were to be found in papers which reported on measuring technique to determine the efficiency of detergents [2], washing performance and consumer satisfaction [4], the water and energy consumption in domestic laundry [6] and the new EU-Energy label for washing machines [10]. Three papers are concerned with hygiene issues during laundering.…”
mentioning
confidence: 99%